2013
DOI: 10.1016/j.nuclphysb.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

NSVZ scheme with the higher derivative regularization for SQED

Abstract: The exact NSVZ relation between a β-function of N = 1 SQED and an anomalous dimension of the matter superfields is studied within the Slavnov higher derivative regularization approach. It is shown that if the renormalization group functions are defined in terms of the bare coupling constant, this relation is always valid. In the renormalized theory the NSVZ relation is obtained in the momentum subtraction scheme supplemented by a special finite renormalization. Unlike the dimensional reduction, the higher deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
247
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(261 citation statements)
references
References 68 publications
(158 reference statements)
11
247
1
2
Order By: Relevance
“…In the Abelian case this was proved in all loops [44,45] and confirmed by an explicit threeloop calculations [44,19,32,46]. For a generic non-Abelian gauge theory the factorization of relevant integrals into integrals of double total derivatives was verified only in the two-loop approximation [47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the Abelian case this was proved in all loops [44,45] and confirmed by an explicit threeloop calculations [44,19,32,46]. For a generic non-Abelian gauge theory the factorization of relevant integrals into integrals of double total derivatives was verified only in the two-loop approximation [47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 91%
“…The difference between the definitions of the RG functions in terms of the bare coupling constant versus renormalized coupling constant is discussed in detail in [19]. In particular, it was demonstrated that the RG functions defined in terms of the bare coupling constant depend on the regularization, but are independent of the subtraction scheme for a fixed regularization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RG functions defined in the standard way in terms of the renormalized coupling constant [37] satisfy the NSVZ relation only in the NSVZ scheme which in this case can be constructed in all orders by imposing simple boundary conditions on the renormalization constants [20,36]. Thus, the NSVZ scheme can be easily constructed with the Slavnov higher derivative regularization.…”
Section: Jhep05(2016)014mentioning
confidence: 99%
“…It is known [36] that the RG functions defined in terms of the bare couplings depend on the regularization, but do not depend on the subtraction scheme for a fixed regularization.…”
Section: Rg Functionsmentioning
confidence: 99%